SETTING RUANG DAN PENGARUHNYA TERHADAP AKSESIBILITAS PARA PENYANDANG CACAT TUBUH DI PUSAT REHABILITASI YAKKUM YOGYAKARTA - Sholahuddin, Muhammad (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2007)
The number of difable persons in Indonesia according to WHO is 7%-10% from totalpopulation and only a small number of them have adequate education and decent job. Thiscondition is due to the lack of accessibility facilities in public spaces and in this condition theyneed an institution or a community which cares and encourages positive attitude. One institutionwhich provides such services is YAKKUMrehabilitation centre located in Yogyakarta. In generalthis research is intended to identity the impact of room setting to accessibility of the difable. Thespecific purpose of the research is to recognize impact of room setting and other factors towarddifable accessibility in YAKKUM. This research uses a deductive method with Applied purposivesampling to ten room based on its tool aid properties. Data were collected with triangulationmethod and analyzed descriptively. SPSS was used to analyze. The quantitative data incomparing factors of room setting which has impact on accessibility. Observed variablesincluding roomsetting (dimension and form, furniture and lay out, and environmental element ofroom). The result of this study shows that the accessibility in receptionist room was influencedby lay out and furniture, lighting, air movement; Office room: lighting, air movement; Class room:lighting and air movement; Library room: furniture and lay out, lighting, air movement; Socialroom: knob, lay out, and lighting; dining room: lay out, lighting and air movement; Laundry room:furniture; Physiotherapy room: knob, furniture and lay out; Hostel room: furniture; and Toiletinfluenced by knob, furniture and lay out, lighting, air movement. This study also found factors ofroomsetting which influenced accessibility for difable in YAKKUM. These factors are the type offurniture, and lay out, lighting, air movement and dimension of switch control.Key Words: Setting Room, Accessibility, Difable